SINERGI MANAJEMEN DAN PENDIDIKAN: Model Pembelajaran yang Menunjang Potensi Siswa - La Hadisi; Erni Qomariyah (Journal Publicuho, 2023)
Effective education in the digital age requires synergy between school management and education to break the 'one-size-fits-all' paradigm. This study aims to analyze the implementation of potential-based learning models at SMPIT Al Qalam Kendari. In the context of Islamic Religious Education, this study particularly highlights the need for a learning approach that not only prioritizes religious knowledge, but also fosters students' emotional, spiritual, and social intelligence. By assessing educational practices that are often monotonous and unable to accommodate the diversity of students' potential, this study examines how innovative and potential-based learning models can overcome the gap between potential and learning outcomes achieved. Effective school management synergies are needed to support these didactic innovations, empower teachers with relevant competencies, and ensure that student-centred learning achieves holistic educational goals. This model is expected to make a significant contribution to developing students' potential as a whole and sustainably.